2006
DOI: 10.1002/mats.200600007
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of Copolymer Composition Distribution in Living Radical Polymerization Using Semi‐Batch Feeding Policies: A Model Simulation

Abstract: Summary: Although controlled/living radical copolymerization has been extensively studied, the control of copolymer composition distribution receives little attention. In this paper, taking RAFT copolymerization as an example, we develop a mathematical model and simulate copolymerization systems with various reactivity ratios. It is demonstrated that through semi‐batch operations with programmed profiles of slow monomer feeding rate, precise control over copolymer composition distribution (uniform and designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 28 publications
2
99
0
1
Order By: Relevance
“…At higher conversions, this concentration drops, due to the volume increase upon monomer addition, and FRP behavior is thus circumvented leading to a good control over polymer properties. However, despite this excellent control, a relatively slow ICAR ATRP is obtained, in agreement with literature reports on related CRP systems [38,39]. It can thus be concluded that the highest linear gradient quality can be obtained using a multi-component fed-batch approach, as it allows tailor-design of linear gradient dormant copolymer chains albeit at the expense of an increase of the polymerization time.…”
Section: Multi-component Fed-batch Procedures For Addition Of Conventisupporting
confidence: 89%
See 2 more Smart Citations
“…At higher conversions, this concentration drops, due to the volume increase upon monomer addition, and FRP behavior is thus circumvented leading to a good control over polymer properties. However, despite this excellent control, a relatively slow ICAR ATRP is obtained, in agreement with literature reports on related CRP systems [38,39]. It can thus be concluded that the highest linear gradient quality can be obtained using a multi-component fed-batch approach, as it allows tailor-design of linear gradient dormant copolymer chains albeit at the expense of an increase of the polymerization time.…”
Section: Multi-component Fed-batch Procedures For Addition Of Conventisupporting
confidence: 89%
“…For "normal" ATRP [38] and RAFT polymerization [39], such Mayo-Lewis based fed-batch additions were already explored with computer simulations, while assessing the overall conversion based on the number average chain length, i.e., assuming controlled conditions, and considering a monomer feed policy in which all of the less reactive comonomer is initially present and only the more reactive comonomer is added along the polymerization. However, in these kinetic studies, in which no explicit calculation of the copolymer composition is included, the fed/semi-batch addition of comonomer is accompanied by a low polymerization rate, a rather high dispersity and a relatively low livingness.…”
Section: Multi-component Fed-batch Procedures For Addition Of Conventimentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous article, we demonstrated by simulation that semibatch RAFT copolymerization with an appropriate monomer feeding policy offers effective control over the copolymer gradient profile. 27 In this work, we develop a kinetic model for semibatch ATRP copolymerization and investigate the effect of comonomer feeding policies on the gradient profile of resulting copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the initiator concentration (see Figure 3c), the curve progression is similar when compared to the monomer concentration as increased backmixing gives higher initiator concentrations. This is reasonable as the consumption rate is proportional to the initiator concentration [Equation (16)]. Concentrations of consumed particles decrease gradually in a system of stirred tanks in series.…”
Section: Cstr-in-series Modelmentioning
confidence: 99%